KOMUNIKASI KRISIS PERAN PEMERINTAH KOTA SEMARANG DALAM PENANGANAN DAMPAK PANDEMI COVID-19 - Elisabeth Sianturi; Adi Nugroho; Agus Naryoso (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2023)
Covid-19, which is caused by a new type of corona virus, was first spread through Wuhan, China at the end of 2019 and spread widely to more than 114 countries. On March 11, 2020, the corona virus was categorized as a global pandemic. Then in April 2020, several countries on the continent of Europe, Asia and America implemented lockdowns where millions of people confirmed to have been exposed to the corona virus had to quarantine (WHO, 2020). The impact of the Covid-19 pandemic so far poses a health risk to the community, has an impact on the economy and also the social environment. This study uses the constructivism paradigm. This research explains that the constructivism paradigm considers social science as a systematic analysis of socially meaningful action through direct and detailed observation of social actors producing and managing everything related to their social life. The results of this study are that the Transformation of Government Public Communication from Crisis Communication to Risk Communication must be carried out not only because of a request from the World Health Organization as an evaluation of government-run communications, but also as a form of improving the Indonesian government's communication strategy in handling COVID-19. -19. The success of risk communication cannot only be seen from the government's public communication strategy through various media. However, what is also important is how the public responds to various information submitted by the government. The public is also expected to play an active role in producing and disseminating information and education needed by all parties who need information from reliable and responsible sources with good and interesting content about various efforts to deal with the COVID-19 pandemic.